Familiarity with digital twin totality: Exploring the relation and perception of affordances through a Heideggerian perspective. (8th March 2022) - Osmundsen, Karen S.; Meske, Christian; Thapa, Devinder
Abstract: The concept of affordances has become central in information systems literature. However, existing perspectives fall short in providing details on the relational aspect of affordances, which can influence actors' perception of them. To increase granularity and specificity in this regard, researchers have suggested that it be supplemented with other concepts or theories. In this article, we argue that the Heideggerian concepts of 'familiarity' and 'referential totality' are well suited for increasing our understanding of the relational aspects of affordances in information systems research. To explore this idea, we conducted a case study of a project concerning the development of a digital twin (i.e., digital representation of a physical asset) in the Norwegian grid sector. We found that users' familiarity with the digital twin totality enabled them to perceive digital twin affordances, and that without this familiarity, affordances remained latent for the users. Through our study, we offer a nuanced perspective on the relational aspect of affordance perception, contributing to affordance theory in that regard. Further, we contribute to practice and information systems research by providing valuable insights into how digital twins are understood and applied in practice.